A bronchogenic cyst presenting as a presternal abscess - Maria Shilova; Marilyn Chiew Lan Wong; Janene Davies; Roy Kimble (Elsevier, 2020)
We present a case of an upper midline pre-sternal abscess in a six-year-old female. The history and clinical examination prompted suspicion of a subcutaneous bronchogenic cyst, which was supported by histology after total excision of the lesion. This article discusses the clinical presentation of this patient, reviews literature on subcutaneous bronchogenic cysts and considers differential diagnoses for the patient's presentation.